2015
DOI: 10.2119/molmed.2012.00336
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Polymorphisms Are Associated with Reduced Esophageal Vitamin D Receptor Expression and Reduced Esophageal Adenocarcinoma Risk

Abstract: Cite this article as: Janmaat VT, et al. (2015) Vitamin D receptor polymorphisms are associated with reduced esophageal vitamin D receptor expression and reduced esophageal adenocarcinoma risk. Mol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Allele frequencies and N total/N deaths for each individual genotype can be found in the Table S1. Allele frequencies and N total/N deaths for each individual genotype can be found in the Table S1. regarded as a negative TF, and although specific information for melanomas is lacking, in esophageal adenocarcinomas the rs1989969-T allele (responsible for greater risk of melanoma death in our study among those with high UVB) was linked to reduction in VDR expression (Janmaat et al, 2015).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Allele frequencies and N total/N deaths for each individual genotype can be found in the Table S1. Allele frequencies and N total/N deaths for each individual genotype can be found in the Table S1. regarded as a negative TF, and although specific information for melanomas is lacking, in esophageal adenocarcinomas the rs1989969-T allele (responsible for greater risk of melanoma death in our study among those with high UVB) was linked to reduction in VDR expression (Janmaat et al, 2015).…”
Section: Discussionmentioning
confidence: 53%
“…The significant rs1989969 is located in an evolutionary conserved region upstream of the translation start, and T‐alleles are responsible for the differential binding of the transcription factor (TF) GATA‐1 to the VDR gene. 33 GATA‐1 is generally regarded as a negative TF, and although specific information for melanomas is lacking, in esophageal adenocarcinomas the rs1989969‐T allele (responsible for greater risk of melanoma death in our study among those with high UVB) was linked to reduction in VDR expression (Janmaat et al., ).…”
Section: Discussionmentioning
confidence: 59%
“…A limitation of our study was that the protein levels of VDR were not determined because of the limited counts of PBMCs. However, previous studies have demonstrated that the mRNA and protein levels of VDR in various tissues, such as placental endothelium, squamous epithelium, and parathyroid cells, exhibited similar trends without in vivo or in vitro intervention . Further studies are needed to validate the concordant results between the mRNA and protein levels of VDR in patients with AA.…”
Section: Discussionmentioning
confidence: 92%
“…[ 34 , 37 39 ] VDR expression is upregulated in BE compared with normal esophageal mucosa,[ 34 , 38 ] suggesting that BE may be more sensitive than normal esophageal mucosa to the effects of calcitriol, the active form of vitamin D. Recent data also suggest that genetic variations in VDR are linked to reduced EAC risk. [ 40 ] Clinically, low vitamin D levels have been associated with insulin resistance and metabolic syndrome,[ 41 ] both of which are common in BE patients. [ 29 , 42 ] Moreover, vitamin D deficiency is associated with an increased risk, as well as worse outcomes, in other cancers.…”
Section: Discussionmentioning
confidence: 99%